The poverty of sustainability: behavioral choices of drinking water in Kenya and Germany - Saravanan, V. Subramanian (Frontiers in Sustainability, 2024)
This paper discusses the poverty of sustainability through a comparative study of drinking water supplies in Kenya and Germany. The poverty of sustainability emerges from the conventional policies of sustainability research and practice, which take an instrumental and mechanistic view while ignoring the micro dimensions of human consciousness, emotions, power relations, and connectedness. This research is directly relevant to the special issue "Exploring Personal Sustainability in the Context of Food Systems." This brief research report is based on empirical research in Kenya as well as an analysis of secondary documents and blogs in Germany on behavioral choices regarding drinking water.